GE_GERICHTE P/15115/2024 vom 20. März 2025 - GE Cour de justice (2025)
VOL(DROIT PÉNAL);CHANTAGE;BRIGANDAGE;INFRACTIONS CONTRE LE PATRIMOINE;TENTATIVE(DROIT PÉNAL);FIXATION DE LA PEINE;EXPULSION(DROIT PÉNAL) | CP.139.ch1; CP.156.ch1; CP.140.ch1; CP.66a.al1.letc